2022
DOI: 10.1007/s12262-022-03308-4
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Outcomes of Surgical Patients Operated During COVID 19: a Single Centre Study

Abstract: COVID-19 pandemic has been widespread and devastating and has created unprecedented challenges for the whole medical fraternity. Mainly emergency surgeries were carried out during the pandemic, and data on postoperative outcomes of COVID-19 patients is limited [1,2]. Hence, this study was planned to find out post-operative outcome of RTPCR-positive COVID-19 patients who underwent emergency surgeries in a tertiary care institute. Retrospective data of those patients which included various parameters such as age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Most global studies on surgical patients showed worse perioperative outcomes in patients with a positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) test [1][2][3][4][5][6]. The few Indian studies that are available also report high morbidity and mortality in COVID-19 patients after surgery but are retrospective in nature [7,8]. Understanding the impact of COVID-19 infection on postoperative morbidity and mortality in surgical patients is vital for evidence-based preoperative risk stratification, shared decision-making, balancing risks with benefits, monitoring trends in postoperative outcomes, and planning surgical services for future pandemics.…”
Section: Introductionmentioning
confidence: 99%
“…Most global studies on surgical patients showed worse perioperative outcomes in patients with a positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) test [1][2][3][4][5][6]. The few Indian studies that are available also report high morbidity and mortality in COVID-19 patients after surgery but are retrospective in nature [7,8]. Understanding the impact of COVID-19 infection on postoperative morbidity and mortality in surgical patients is vital for evidence-based preoperative risk stratification, shared decision-making, balancing risks with benefits, monitoring trends in postoperative outcomes, and planning surgical services for future pandemics.…”
Section: Introductionmentioning
confidence: 99%